On a Generalized Semicommutative Ring - Mustafa D. AL-Obaidi; Sinan O. AL-Salihi (Tikrit Journal of Pure Science, 2019)
Let R be a ring with identity. In this paper, we introduce some new results in a class of rings which refers to generalization of semicommutative rings called Q-semicommutative rings whenever x2=0 implies xRx=0, for any a ∈R [7]. They study investigates general properties of Q-semicommutative rings and shows several results of semicommutative ring can be extended to Q-semicommutative rings